Pengaruh Bahasa Pertama (Bahasa Sasak) Terhadap Perkembangan Bahasa Anak dalam Lingkungan Keluarga di Desa Pelembak - Wahidah, Yulia (Lembaga Publikasi Ilmiah Nusantara, 2024)
The aim of this research is to explain the influence of the first language (Sasak language) on children's language development in the family environment in Pelembak Village. Sasak language is the regional language of the Sasak tribe used by people on the island of Lombok. The Sasak language has a diversity of dialects. This language is related to Balinese and Javanese and belongs to the Austronesian language family. This research uses qualitative research methods. Using observation, interview and documentation data collection techniques. The data sources in this research were 11 children from 11 selected heads of families in Gunung Malang Hamlet, Pelembak Village. Of the 11 heads of families, the research objects were children aged 2-4 years in several families. This is based on the influence of the first language on the child's language through the family environment which researchers have observed during observations and by looking at their linguistic background. The data analysis technique is conducting interviews to collect data and then carrying out reductions (summaries) to create a research focus, then the researcher describes the data in the form of interviews and then concludes to present the research results. Based on the results of this research, it was found that the first language (Sasak language) greatly influences children's language development in the family environment in Pelembak Village. This results in weak mastery of the Indonesian language. The factors that influence the first language (Sasak) on children's language development in the family environment in Pelembak Village are: parental, family, social environment, education and technology factors.